Study of Plasma Diffusion in DC Glow Discharge Using Optical Emission Spectroscopy - Kadhim, Murad M.; Abbas, Qusay A. (Iraqi Journal of Science, 2026)
This study focused on plasma diffusion to understand how gas pressure affects diffusion dynamics. Experimental measurements were carried out to assess the electron temperature, electron number density, drift velocity, particle flux, growth rate, diffusion coefficient, and constant time decay as a function of gas pressure. The results showed that while the electron number density (ne) grows with increased gas pressure, the electron temperature (Te) of the plasma falls. The results indicated that gas pressure significantly influences plasma behavior, with a notable decrease in diffusion coefficients and constant time decay as gas pressure rises from 0.04 to 0.4 mbar. The stability and diffusivity of the plasma are affected by bumping effects, which are enhanced by increased gas pressure. This study advances our knowledge of plasma behavior in DC glow-discharge systems by emphasising the relationship between gas pressure and plasma dispersion.